2009
DOI: 10.1124/mol.108.053876
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a Class A G Protein-Coupled Receptor Oligomer Interface

Abstract: The quaternary structure of G protein-coupled receptors (GPCRs) can influence their trafficking and ability to transduce signals. GPCR oligomers are generally portrayed as long-lived entities, although the stability of these complexes has not been studied. Here we show that D2 dopamine receptor protomers interact transiently at a specific oligomer interface. Selective immobilization of cyan fluorescent protein-D2 receptors (CD2Rs) in the plasma membrane failed to completely immobilize coexpressed D2-venus rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 14 publications
6
64
2
Order By: Relevance
“…The content of monomeric versus dimeric receptors in the membrane has been difficult to study, and this is not known for any family B GPCR. Recent work with family A receptors suggests that many GPCRs exist in a dynamic equilibrium between monomeric and dimeric states, with the stability of dimeric complexes differing for individual receptor subtypes (12)(13)(14)(15). Nonetheless, even for highly transient interactions, such as those seen for FPR receptors, the mean residence time for interaction (∌90 ms) (15) would allow for coupling to and activation of G proteins (40-70 ms) (44,45), consistent with dimerization playing an important role in the efficiency of G-protein coupling and, indeed, in differentiating strength of stimulus and pleiotropic receptor coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of monomeric versus dimeric receptors in the membrane has been difficult to study, and this is not known for any family B GPCR. Recent work with family A receptors suggests that many GPCRs exist in a dynamic equilibrium between monomeric and dimeric states, with the stability of dimeric complexes differing for individual receptor subtypes (12)(13)(14)(15). Nonetheless, even for highly transient interactions, such as those seen for FPR receptors, the mean residence time for interaction (∌90 ms) (15) would allow for coupling to and activation of G proteins (40-70 ms) (44,45), consistent with dimerization playing an important role in the efficiency of G-protein coupling and, indeed, in differentiating strength of stimulus and pleiotropic receptor coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an increasing body of evidence supporting dimerization of GPCRs as a widespread feature of GPCR biology, including numerous studies on family A GPCRs, whether these are stable, transient, constitutive, or ligand dependent, and how they impact on receptor function and drug discovery are less clear, and general rules for oligomeric behavior are not evident (9)(10)(11)(12)(13)(14)(15)(16). Even where effects on signaling are studied, these are generally linked to a single pathway and the role of dimerization in the control of receptor engagement and preference for distinct intracellular signaling intermediates (i.e., signal bias) is virtually unstudied.…”
mentioning
confidence: 99%
“…The tetramers of Cy3-and Cy5-tagged ␀ 2 -adrenergic receptors that were identified upon reconstitution of the purified receptor in phospholipid vesicles exhibited an increase in FRET efficiency in the presence of the inverse agonist carazolol, suggesting the formation of larger aggregates such as octamers (58). In the case of oligomers formed by the D 2 dopamine receptor, measurements of fluorescence recovery after photobleaching have suggested that at least one interface is sufficiently unstable that immobilized protomers do not affect the mobility of others (65). If oligomers of the M 2 receptor indeed dissociate and reassociate in a spontaneous manner, the failure to detect monomers in the context of the present model suggests that the system exists predominantly in the oligomeric state.…”
Section: Table 3 Lifetimes and Fret Efficiencies Estimated By Means Omentioning
confidence: 99%
“…Receptor Immobilization by Antibody Cross-linking-Immobilization of GFP PTHR at the cell membrane was performed as described (33). Briefly, medium was removed, and the cells were washed three times with buffer containing 150 mM NaCl, 10 mM Na-HEPES, 12.8 mM D-glucose, 2.5 mM KCl, 0.5 mM MgCl 2 , and 0.5 mM CaCl 2 , pH 8.0, at room temperature.…”
Section: Methodsmentioning
confidence: 99%